Spatial Variability of Saturated Hydraulic Conductivity in a Karstic Environmental Protection Area - Valadares, Emerson Vinicius (2022)
Saturated hydraulic conductivity (Ksat) is a fundamental property to understand water and solute dynamics in saturated and unsaturated soils. The objective of this study is to present and assess the results of a statistical analysis of the data obtained from the determination of the permeability of a variety of soils (Argisols, Latosols, Gleysols, and Cambisols) of the Lagoa Santa Karst Environmental Protection Area (State of Minas Gerais, Brazil). Software R version 4.0.4 was used for the statistical analyses. Argisol, Cambisol, and Gleysol samples yielded normal conductivity distributions at depth, with mean values of 1.16 x 10-1 m/d, 6.14 x 10-2 m/d, and 1.95 x 10-3 m/d, respectively. Regarding the log-normal distributed Latosol samples P48 and P52 and Gleysol sample P54sup, it was concluded that probability, respectively of 85.72%, 96.55%, and 47.37%, exists for hydraulic conductivity values between 0.1 x 10-1 m/d and 4 x 10-1 m/d to occur. Studies or criteria to establish Ksat values that should be really representative of the whole study area have not been found. It was preferable to characterize Ksat in terms of levels of probability of occurrence rather than values, such as the mean or median, in order to represent an area that will be subject to the same water flow control operations (irrigation and drainage practices, leaching and erosion control, etc.). Therefore, it is not appropriate to assume a normal distribution of saturated hydraulic conductivity values for areas with the characteristics of Lagoa Santa.